Pengaruh Metode Pemberian Tugas (Take Home) Terhadap Minat Belajar Anak Kelompok B Di Tk Dharma Wanita Gedangan Mojokerto - Indri Dwi Isnaini (Universitas Islam Lamongan, 2018)
One of the external factors that affect the child's interest in learning is the assignment of homework or homework. According to Muijs, et al (2008: 150)